The Influence of Family Environment, Self-Efficacy, and Campus Brand Image on The Interest of Vocational School Students in Continuing Their Education to University - Destya Fitryana; Santi Susanti; Susi Indriani (INDO PUBLISHING, 2025)
This study aims to examine the influence of family environment, self-efficacy, and campus brand image on vocational high school students' interest in continuing their education to college. The study population consisted of 324 students, with a sample of 179 respondents obtained through proportional random sampling. This study employs a quantitative approach using a survey method through the distribution of questionnaires. Data were analyzed using descriptive statistics, validity and reliability tests, normality and linearity tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results of the study indicate that, partially, family environment, self-efficacy, and campus brand image have a positive and significant influence. Simultaneously, they have a positive and significant influence on students' interest in continuing their education at university.